2019
DOI: 10.1080/21505594.2019.1640035
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles of the anaphylatoxin receptors C3aR, C5aR1 and C5aR2 in experimental meningococcal infections

Abstract: The complement system is pivotal in the defense against invasive disease caused by Neisseria meningitidis (Nme, meningococcus), particularly via the membrane attack complex. Complement activation liberates the anaphylatoxins C3a and C5a, which activate three distinct G-protein coupled receptors, C3aR, C5aR1 and C5aR2 (anaphylatoxin receptors, ATRs). We recently discovered that C5aR1 exacerbates the course of the disease, revealing a downside of complement in Nme sepsis. Here, we compared the roles of all three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 83 publications
(123 reference statements)
2
25
0
1
Order By: Relevance
“…To overcome this safety burden, direct inhibition of C5a or C5aR1 would allow for anti-inflammatory activity in diseases mediated by the anaphylatoxin without compromising MAC formation. In addition, inhibition of the C5a–C5aR1 axis has been found to alleviate Neisseria -induced sepsis in mice ( 190 ). Moreover, C5a generated through direct C5 cleavage by proteases other than C5 convertase can be neutralized with agents directly targeting the C5a-C5aR1 axis ( 191 ).…”
Section: Terminal Complement Pathway-targeting Treatments Of Inflammamentioning
confidence: 99%
“…To overcome this safety burden, direct inhibition of C5a or C5aR1 would allow for anti-inflammatory activity in diseases mediated by the anaphylatoxin without compromising MAC formation. In addition, inhibition of the C5a–C5aR1 axis has been found to alleviate Neisseria -induced sepsis in mice ( 190 ). Moreover, C5a generated through direct C5 cleavage by proteases other than C5 convertase can be neutralized with agents directly targeting the C5a-C5aR1 axis ( 191 ).…”
Section: Terminal Complement Pathway-targeting Treatments Of Inflammamentioning
confidence: 99%
“…6 and 7). The singular and combined effects of C5aR1 and C5aR2 have been elucidated in a range of biological responses [44][45][46] . Mice deficient in C5aR1 or C5aR2 were used in this regard to distinguish between their effects, because NoxD21 practically blocks the www.nature.com/scientificreports/ activity of both these receptors concomitantly.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in LPS-induced shock with systemic inflammation demonstrated an early enhanced lethality rate of C3aR-deficient mice, but after a 72-h observation period, no changes could be detected between the wild-type and C3aR-deficient littermates [32]. In experimental meningococcal sepsis, a differential role for the C3aR and the C5a receptors has recently been reported: whereas C5aR1 and C5aR2 aggravated the disease immune pathology, C3aR was rather protective [33]. Thus, C3a seems to reveal some protective effects, possibly by activating the hypothalamus-pituitary-adrenal axis and by inhibition of neuronal cell death [32].…”
Section: Rodentsmentioning
confidence: 99%